Tectono-metamorphic evolution and significance of shear-zone lithologies in Akebono Rock, Lützow-Holm Complex, East Antarctica - Baba, Sotaro; Hokada, Tomokazu; Kamei, Atsushi; Kitano, Ippei; Motoyoshi, Yoichi; Nantasin, Prayath; Setiawan, Nugroho Imam; Dashbaatar, Davaa-Ochir (Antarctic Science, 2020)
We describe a major shear zone exposed at Akebono Rock and discuss its deformation and metamorphic history, with a view to providing a better understanding of the geological history of the Lützow-Holm Complex. Three deformation episodes are recognized: D1 produced open folds (F1), boudinage and a regional ductile foliation, whilst the related metamorphic facies is characterized by stable garnet. F1 folding is dominantly preserved in the eastern part of the study area. During D2, an isoclinal to tight asymmetric F2 folds developed mainly in the west part of the region, accompanied by an S2 shear, under biotite facies retrograde metamorphism. The D3 episode involved the formation of the major shear zone, characterized by mylonite and L-tectonite fabrics, which took place at ~610–660°C and 4–5 kbar. Large, sigmoidal garnet core domains have S-shaped inclusion trails, suggesting that syntectonic garnet growth occurred before the formation of the shear zone. Estimated P-T conditions suggest that the sigmoidal garnet-bearing amphibolite was recrystallized at a deeper crustal level and was brought to a higher level during the formation of the shear zone. Crustal-scale deformation involving syntectonic recrystallization and shearing of Akebono Rock is a key issue for reconsidering the evolution of the Lützow-Holm Complex. http://purl.org/coar/resource_type/c_6501